THE EFFECTIVENESS OF YELLOW CARD (AK-1) MAKING SERVICES THROUGH THE APPLICATION OF EMPLOYMENT INFORMATION SYSTEMS (SISNAKER) - M. Rival Kustiyawahyudi; M. Rijal Amirulloh; Yana Fajar FY. Basori (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The topic of this research is about the effectiveness of public services in the employment sector. This research was motivated by the existence of an Employment Information System (SISNAKER) which was created as an online- based platform created to respond to the demands of a changing world that leads to automation and digitization, especially regarding the implementation of a yellow card (AK-1) making services for job seekers. The results of this study indicate that to respond to changes in the service system, the Manpower Office (Disnaker) of Sukabumi City as a local government agency that issues a yellow card (AK-1), always seeks to improve the skills in using the system for operators. With these skills, the implementation of yellow card services (AK-1) through SISNAKER in Sukabumi City becomes easier and more flexible. Besides being used to access the yellow card (AK-1) service, SISNAKER is also integrated with various job vacancies and job training information that can be accessed by job seekers in Sukabumi